From Free to Civilized Markets: First Steps towards Eutopia - Jakob Kapeller; Bernhard Schütz; Dennis Tamesberger (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2014)
Unfettered market forces tend to violate basic universal concepts like justice, dignity or fairness. Therefore we suggest moving to a new concept of markets, which we label 'civilized markets'. A civilized market tries to ensure that free entrepreneurship and open markets are eventually compatible to these basic and universal values that also serve as moral cornerstones of the European project. We propose to establish a new European institution that should set and enforce minimum standards for goods sold on the European market in order to accomplish what we call a 'civilized market'.
Keywords: 330; European Union; international trade; social embeddedness; market regulation; labor standards; sustainability; product quality; Top Runner Program